2010
DOI: 10.1590/s1676-06032010000400034
|View full text |Cite
|
Sign up to set email alerts
|

Estuarine ichthyofauna of the Paraguaçu River, Todos os Santos Bay, Bahia, Brazil

Abstract: Estuaries are areas of recognized importance in the development and sanctuaries of fishes and also a great source of fishing resources. This article presents an inventory of fishes from the Paraguaçu River estuary, Todos os Santos Bay, Bahia, Brazil. 28 points comprising the saline sections that may exist in a tropical estuary were sampled quarterly from March 2009 to February 2010 with the aid of bottom gill nets, surface gill nets, seine net and casting net. A total of 4.097 individuals were captured, belong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 31 publications
1
21
0
2
Order By: Relevance
“…Although many studies of Brazilian estuaries have classified species into functional guilds (VIEIRA; MUSICK, 1993;BOUCHEREAU, 2004;ANDRADE-TUBINO et al, 2008;REIS-FILHO et al, 2010;VILAR et al, 2011), they have not tested the effect of the estuarine salinity gradient on the functional traits of the assemblages. We found that traditional taxonomic metrics were a better indicator of structural changes than were trophic groups or membership in categories of estuarine use.…”
Section: Discussionmentioning
confidence: 99%
“…Although many studies of Brazilian estuaries have classified species into functional guilds (VIEIRA; MUSICK, 1993;BOUCHEREAU, 2004;ANDRADE-TUBINO et al, 2008;REIS-FILHO et al, 2010;VILAR et al, 2011), they have not tested the effect of the estuarine salinity gradient on the functional traits of the assemblages. We found that traditional taxonomic metrics were a better indicator of structural changes than were trophic groups or membership in categories of estuarine use.…”
Section: Discussionmentioning
confidence: 99%
“…This is, in part, a result of the intermediate physicochemical characteristics found at the site, which ranged between a typical and an estuarine beach, and favored the occurrence of estuarine species at the site (e.g. S. testudineus, S .greeleyi, Cathorops spixii, Atherinella brasiliensis, Achirus lineatus, Anchoa januaria, Anchoa tricolor, Diapterus rhombeus, Cynoscion microlepidotus, Stellifer stellifer) (GARCIA; VIEIRA, 2001;BARLETTA et al, 2008;REIS-FILHO et al, 2010;VILAR et al, 2011a). However, the low energy of the study site allowed for the use of a capéchade net (visibly efficient in other low-energy environments) for the samplings (IGNÁCIO; SPACH, 2009;VASLET et al, 2010).…”
Section: For S Testudineus S Greeleyi and G Genidens On A Tidal mentioning
confidence: 99%
“…In lower latitudes L. grossidens has usually been described as marine migrant or marine straggler (Vasconcelos-Filho & Oliveira 1999, Krumme et al 2004, Sánchez-Botero et al 2008, Reis-Filho et al 2010, Vilar et al 2011, although spawning activities were never reported for lower or higher latitudes in the marine environment. In contrast, the species shows the proven ability to reproduce in both fresh water (Fuster de Plaza & Boschi 1961, Oliveira 1997, Lepkoski et al 2005) and estuarine environments (Ramos 2005, Oliveira 2008).…”
Section: Final Conclusion and Future Research Directionsmentioning
confidence: 99%